Penggalangan Dana dan Pemberian Santunan Kepada Korban Banjir di Medan Oleh Tim Peduli UISU - Jalilah Ilmiha; Lusi Elviani Rangkuti; Farida Khairani Lubis (Medan Resource Center, 2021)
In the last few weeks, it has been raining frequently in Medan and its surroundings. The intensity of the rain that falls is high enough to cause natural disasters such as floods and landslides. It is estimated that there are seven areas affected by flooding. This flood caused various difficulties among the people. Difficulties are in the form of, the difficulty of clean water, blankets, clothes and so on. In addition, the economic impact is also affected by flooding. Many agricultural land sectors were flooded, so many people failed to harvest. This paper aims to realize concern by helping others, getting used to giving alms, increasing ukhuwah Islamiyah, easing the burden on residents of flood victims and strengthening solidarity and togetherness with the people. The method used in this activity is fundraising for flood victims to the University for leaders/institutions and faculty leaders throughout UISU, through cellphones. If the funds have been collected, the team immediately comes to the destination, both at the rectorate and the faculty so that the collected funds can be recorded immediately. then with a certain duration of time, the granting of funds to the party who is entitled/deserves to receive it is carried out according to the results of the team's assessment which ends with taking documentation as evidence of the activity. Fundraising and providing compensation is UISU's contribution in supporting and assisting government programs for the benefit of the people.